CSRouter:router architecture for service extensibility - Gao-feng LV; Zhi-gang SUN; Yu-xian LIN; Yi-jiao CHEN; Tao LI (Tongxin xuebao)
The development of network applications ,network end-end“channel”for data transmission impeded applications,network“platform”integrating computing and storing resource with routers is a considerable efficient means to enhance the efficiency of the network transport.System area network of routers based on high performance unified switching technology is introduced to connect forwarding elements,computing elements and storing elements.The prototype were designed and implemented based on the NetMagic platform of network innovation and the IEF switch system.The testing of packets caching proves that system area network provides high performance and high reliability network bandwidths between forwarding elements and computing elements,and the novel router architecture based on system area network could utilize additional computing and storing resources to process IP packet in depth to accelerate network applications.